VLSI and post-CMOS electronics. Volume 1 Design, modelling and simulation - Dhiman, Rohit; Chandel, Rajeevan (The Institution of Engineering and Technology, 2019)
VLSI and Post-CMOS Electronics is a useful reference guide for researchers, engineers and advanced students working in the area of design and modelling of VLSI and post-CMOS devices and their circuits
Keywords: Integrated circuits -- Very large scale integration.; Metal oxide semiconductors, Complementary.; elektronické knihy; electronic books